2013
DOI: 10.1002/hbm.22250
|View full text |Cite
|
Sign up to set email alerts
|

An independent components and functional connectivity analysis of resting state fMRI data points to neural network dysregulation in adult ADHD

Abstract: Spontaneous fluctuations can be measured in the brain that reflect dissociable functional networks oscillating at synchronized frequencies, such as the default mode network (DMN). In contrast to its diametrically opposed task-positive counterpart, the DMN predominantly signals during a state of rest, and inappropriate regulation of this network has been associated with inattention, a core characteristic of attention-deficit/hyperactivity disorder (ADHD). To examine whether abnormalities can be identified in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
111
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 74 publications
14
111
1
Order By: Relevance
“…Specially, the significant correlations between fDMN and performance IQ might reflect the dysfunction of facial and emotional recognition in ADHD [30]. The significantly altered correlations between WMN and performance IQ might reflect the dysfunction of left dorsolateral prefrontal cortex in ADHD [4,15].…”
Section: Discussionmentioning
confidence: 99%
“…Specially, the significant correlations between fDMN and performance IQ might reflect the dysfunction of facial and emotional recognition in ADHD [30]. The significantly altered correlations between WMN and performance IQ might reflect the dysfunction of left dorsolateral prefrontal cortex in ADHD [4,15].…”
Section: Discussionmentioning
confidence: 99%
“…It is active in a state of rest and deactivated during tasks that make cognitive demands, with stronger deactivation corresponding to increasing attentional demands. 48,49 Increasingly, ADHD is considered as a DMN disorder 50 in which attentional lapses derive from an inappropriate persistence of DMN activation 49 ; for example, a study using a stop signal task found that failure to suppress the DMN was associated with greater errors. 51 Recent pathophysiological models of ADHD recognize it as a disorder encompassing large-scale neural networks, such as the cognitive control network and limbic networks, not only abnormal connectivity within the DMN itself.…”
Section: Discussionmentioning
confidence: 99%
“…6 Another study that included two groups of medication naïve adults with ADHD reported increased connectivity between the DMN and a small region within left lateral PFC based on independent component analysis ( Figure 3). 7 In addition, higher levels of resting state activity within that area of PFC were associated with lower levels of performance on an attentional tasks. Increased connectivity between some DMN areas in ADHD relative to controls has also been reported.…”
Section: Neurobiologymentioning
confidence: 99%
“…A resting state fMRI study in medication naive adults with ADHD reported positive connectivity between an area in lateral prefrontal cortex and default mode network areas identified by independent component analysis. 7 The location and extent are approximated on a lateral view of the cortical surface (violet). Higher resting state activity in this region was inversely correlated with attentional performance (higher activity, lower performance).…”
mentioning
confidence: 99%